Alat fisioterapi untuk keputusan pemulihan yang lebih pantas : kajian kes pesakit yang mengalami patah kaki - Andikurniawan, Bin Samsuar (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research is to facilitate the recovery of patients who suffer from inadequate medical care and the increasing number of patients who suffer from bone fractures. This new device could enhance the recovery period of the bone fracture patient.